Uncertainty in Measurements in Medical Laboratories / A Narrative Review by the Staff of the New Najran General - Shaheen masoud ali alyami; Ali Rashed Ali Alabbas; Faisal zidan ali Aldoushan; Ayed misfer hadi al saleem; Sari ahmed salem al sari; Abdullah Hamad Mohammed Alqahtani; Ali Faisal Ali Alshareif; Hassan Hussein ali almakrami; Mohammed Hamad Al Mansour; Ahmad Mohmmad Saleh Al harsan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Quantitative laboratory tests are important in identifying approximately 70% of medical decisions made by physicians regarding diagnosis, treatment, hospital admission, and discharge. Thus, it is of utmost importance to measure correctly and to rely on test results. Laboratories give the right results when measurement is performed under optimal conditions, with the correct method, using the right equipment, and proper reference materials. These parameters focus on accuracy. In addition, the concept of measurement uncertainty also focuses on accuracy as recorded in the standard definitions as the "parameter associated with the result of a measurement which characterizes the dispersion of the values that could be reasonably attributed to the measurand." To assure the reliability of all results, it is necessary to state whether the measurement has been performed well, i.e., to answer the question, "Is the result okay?" The concept of measurement uncertainty offers the correct answer. It is considered that when the correct determination of the uncertainty of a measurement indicates a realization of uncertainty at least partially reflected in the test report, the result becomes acceptable, making it easy to decide whether the results fall within the limits described. If the result is not within the limits, evaluations can indicate the adequacy or inadequacy of the result and, consequently, the adequacy or inappropriateness of the criteria for evaluation, to assess whether the possibility of the analyte in question is within acceptable limits of operation.